PANDANGAN POLITIK AHLUS SUNNAH TERHADAP PENGUASA - Semjan Putra, Ali Musri (Sekolah Tinggi Dirasat Islamiyah Imam Syafi'i Jember, 2013)
Islam as a religion that has been perfectly set up various problems of his people. Starting from the problem of belief, worship, muamalah, morals until the issue of the relationship between rulers and ruled. Anyone who tried to examine this issue through our books written by scholars from time to time, he will find how Islam has given the concept of the best in this regard. But the lack of information that is held by some people cause they view the concept of Islam with one eye on this. In this paper I will describe the various arguments of the Qur'an and Sunnah that explains it. Key word: Politik, Ahlus Sunnah, Penguasa.